Sentiment Analysis Based on Appraisal Theory for Assessing Incumbent Electability - Canrakerta Canrakerta; Pamuji Lasiyanto Putro; Zikri Irfandi; Nur Fitriah Ayuning Budi; Achmad Nizar Hidayanto (IAES Indonesia Section, 2018)
Sentiment analysis is a useful study for determining opinions by classifying text. The document used in the research comes from Twitter about public opinion about community satisfaction related to performance of incumbent. The method used is Appraisal Theory. The data used are 1587 for Jokowi related data, 1774 for Ministry related data, and 1337 government related data. The result of data analysis from this research is that people have positive sentiments for incumbent. Innovation is a term that has the highest positive sentiment, whereas imaging is the term that has the lowest negative sentiment.